The Technology and Application of Hydroponic Vegetable Cultivation Systems Based on Solar Power Plants as an Effort to Fulfill Vegetable Needs Independently - Siti Sunariyati; Rasidah Rasidah; Wilson Jefriyanto; Yunus Pebriyanto (Universitas Lambung Mangkurat, 2024)
The problems found at SMP Negeri 10 as the location of community service are that the condition of the land is less fertile, there is a lack of knowledge and skills regarding cultivation using a hydroponic system, and it is located in a remote area so that the vegetables consumed have always been imported from Palangka Raya City with a travel time of 1.5 hours by land and river. Electricity blackouts often occur in this area, which is quite disruptive to residents' activities. The solution to overcoming the problem is to use a hydroponic farming system that uses alternative electrical energy from solar power plants (PLTS). PLTS can be used as an alternative electrical energy source to run a hydroponic system. This PLTS was chosen because the Central Kalimantan region is a tropical area that effectively absorbs sunlight. This community service activity (PkM) aims to increase high school students' knowledge, skills, and interest in modern vegetable cultivation. The PkM team creates a guidebook to aid in the operation of hydroponic cultivation and the PLTS system, integrating training activities into project-based Merdeka Belajar activities during the implementation of community service. Monitoring and evaluation were carried out regularly until after the harvest period, and the results showed that student understanding increased to the medium-high category and attracted student interest to the excellent category.